Financial effects of open innovation in the manufacturing companies in Malacca, Malaysia / Mohd Fazli Mohd Sam, Nanthakumar Subramanian and Raihayu Mustafa - Mohd Sam, Mohd Fazli; Subramanian, Nanthakumar; Mustafa, Raihayu (Universiti Teknologi Mara, Cawangan Melaka, 2017)
Companies must use their resources effectively and productively if they are to compete in an increasingly competitive globalized economy. Effective performance measurement can support this competitiveness. To be able to do this, companies must know the factors that influence their performance and manage these factors in an effective manner. This study seeks to investigate the effect of open innovation strategies of manufacturing companies on their financial performance. A total of 2 manufacturing companies that are registered under the Companies Commission of Malaysia, were selected and their managers have been interviewed. It was found, that an increase in the quality and cost/flexibility will increased the financial performance. However, the rate of delivery did not have any influence on the financial performance. On the basis of the analysis and interviewed data done on the firm size, the last finding is that the effect of the quality and cost, flexibility on financial performance is higher for manufacturing companies. The paper identifies the open innovation strategies in manufacturing that significantly influence the financial performance of manufacturing companies.